Effect of Aripiprazole on Anxiety Associated With Ethanol Physical Dependence and on Ethanol-Induced Place Preference - Masahiro Shibasaki; Kazuhiro Kurokawa; Koji Mizuno; Seitaro Ohkuma (Elsevier, 2012)
In the present study, we investigated the effect of aripiprazole, a dopamine system stabilizer, on ethanol-induced psychological and physiological dependence and anxiety-like behavior. First we determined the effect of aripiprazole, a dopamine system stabilizer, on the development and expression of ethanol-induced place preference. Both the development and expression of ethanol-induced place preference was significantly suppressed by treatment of aripiprazole. Next, the withdrawal score gradually increased with increasing duration after the withdrawal from ethanol for 6 days in vehicle-treated mice and the maximal score was observed 10 h after the ethanol withdrawal. Aripiprazole caused no changes in the withdrawal score as compared to vehicle-treated mice. Under these conditions we investigated the effect of aripiprazole on the anxiety-like behavior of ethanol physical dependent mice, which were animals subjected to ethanol vapor for 6 days. The significant decrease of time spent in the open arms and number of open arm entries characterize the anxiety-like behavior in ethanol physical dependent mice, compared to control mice. These decreases were reversed by treatment of aripiprazole, which were inhibited by WAY100635, a serotonin 5-HT1A receptor antagonist. The present findings suggest that aripiprazole was efficient for reversing ethanol-induced place preference and anxiety-like behavior. Keywords:: aripiprazole, alcohol dependence, anxiety, place preference